Perbandingan Jumlah Total Bakteri pada Penggunaan Wadah Penyimpanan Air Susu Ibu (ASI) yang Berbeda - Dwimei Ayudewandari Pranatami (Al-Hayat: Journal of Biology and Applied Biology, 2020)
At the beginning of its life, breast milk is the best food for babies because breast milk contains all the nutrients that can be used for optimal growth and development of the baby. Therefore, the government has promoted exclusive breastfeeding programs for infants 0-4 months or up to 6 months if possible. However, the current phenomenon especially among working mothers, there are regulatory difficulties in giving milk to children. Breast milk can still be given by a working mother the pumping method and stored first. To facilitate the storage of breast milk, three types of containers are widely used, namely plastic clips, plastic bottles, and glass bottles. In the period of storage, it must be ensured that breast milk can be maintained with good quality and integrity. This study aims to compare the total number of bacteria that can grow in breast milk after being stored in three different types of containers. The sampling technique used in this study is total sampling. The treatment in this study was by placing breast milk in three different containers, namely plastic bottles (A), glass bottles (B), and plastic bags for storing breast milk (C) stored at room temperature (16-260C) with three replications. Breast milk is obtained from volunteers who have been predetermined and then accommodated in sterile containers. Statistical test results showed that the variation of the container did not affect the total bacterial colony with a p-value of 0.246 (P 0.05) with the highest number of bacteria in plastic bag storage with an average of 5.4x103 CFU/ml.